2018
DOI: 10.1017/aog.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal seismicity cycle linked to subsurface melting on an ice shelf

Abstract: Seismograms acquired on the McMurdo Ice Shelf, Antarctica, during an Austral summer melt season (November 2016–January 2017) reveal a diurnal cycle of seismicity, consisting of hundreds of thousands of small ice quakes limited to a 6–12 hour period during the evening, in an area where there is substantial subsurface melting. This cycle is explained by thermally induced bending and fracture of a frozen surface superimposed on a subsurface slush/water layer that is supported by solar radiation penetration and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 71 publications
3
39
0
Order By: Relevance
“…At temperature of −5 • C, Mellon (1997) and Petrich et al (2015) approaches lead to Young's modulus of approximately 4.2 and 6.0 GPa, respectively, which is consistent with a constant value of 5 GPa used by MacAyeal et al (2019) for estimating diurnal thermal bending moment of an ice plate.…”
Section: Appendix: A: Empirical Temperature Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…At temperature of −5 • C, Mellon (1997) and Petrich et al (2015) approaches lead to Young's modulus of approximately 4.2 and 6.0 GPa, respectively, which is consistent with a constant value of 5 GPa used by MacAyeal et al (2019) for estimating diurnal thermal bending moment of an ice plate.…”
Section: Appendix: A: Empirical Temperature Modelsupporting
confidence: 78%
“…Sea ice thermal-contraction cracking at such relatively modest temperatures might be due to thermal bending, which intensifies the stress (Bazant, 1992). Similarly, the thermal bending of a frozen lid overlying slushy ice/water was associated with seismicity on an ice shelf in Antarctica (MacAyeal et al, 2019). To our knowledge, with the exception of a study in Tibet by Zhang et al (2019), the thermal contraction cracking of glacier ice has not been observed at temperate alpine glaciers (Neave & Savage, 1970) or in the ablation zone of the Greenland Ice Sheet, where dynamic stresses and hydrofracturing are dominant (Röösli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Jacking accompanied by seismicity is reported during rapid drainage events of supraglacial lakes (Das et al, 2008;Doyle et al, 2013). We also note that high occurrence rates of overlapping fracturing icequakes may result in sustained tremor-like fracturing events (Podolskiy et al, 2018;MacAyeal et al, 2019).…”
Section: Introductionmentioning
confidence: 61%
“…We expect that conduits tend to close due to ice creep as discharge decreases at the end of the drainage. However, we note that the contraction of conduits takes place on the order of days to weeks, especially for thin ice (less than 100 m) as encountered on Glacier de la Plaine Morte (Mathews, 1973). This suggests that our inferred closure rates of the relative hydraulic radius (Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation